1987
DOI: 10.1002/1097-0142(19871101)60:9<2156::aid-cncr2820600906>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin and 5-fluorouracil in the primary management of squamous esophageal cancer

Abstract: A combined treatment program consisting of chemotherapy with cisplatin and infusion 5-fluorouracil (5-FU) for three cycles followed by esophagectomy or radiation, or both, has been conducted in 26 patients with squamous cancer of the esophagus localized to the primary site. Eleven patients had objective evidence of partial or complete response to the chemotherapy. Fourteen patients were operated on and ten underwent total esophagectomy. Drug toxicity was considerable with severe mucositis and myelosuppression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(41 citation statements)
references
References 6 publications
0
41
0
Order By: Relevance
“…(Table 7) Patients with systemic metastatic disease are recommended to receive systemic chemotherapy. The regimen of fl uorouracil plus cisplatin (FP) is considered to be the standard, based on earlier trials in patients with squamous cell carcinoma [60,61]. Phase III trials performed in Japan show that the response to FP therapy does not differ between the histological types, with a response rateof 33.3% in squamous cell carcinoma (JCOG 9407 Hazard ratio in the oxaliplatin group, as compared with the cisplatin group [62) and a response rate of 34% in adenocarcinoma (JCOG 9205).…”
Section: Multimodal Treatmentmentioning
confidence: 99%
“…(Table 7) Patients with systemic metastatic disease are recommended to receive systemic chemotherapy. The regimen of fl uorouracil plus cisplatin (FP) is considered to be the standard, based on earlier trials in patients with squamous cell carcinoma [60,61]. Phase III trials performed in Japan show that the response to FP therapy does not differ between the histological types, with a response rateof 33.3% in squamous cell carcinoma (JCOG 9407 Hazard ratio in the oxaliplatin group, as compared with the cisplatin group [62) and a response rate of 34% in adenocarcinoma (JCOG 9205).…”
Section: Multimodal Treatmentmentioning
confidence: 99%
“…In squamous cell carcinoma of the head and neck very high response rates have been observed when the drug is combined with cisplatin (CDDP) (Thyss et al, 1986b;Amrein & Weitzman, 1985;Kish et al, 1982). This combination protocol is accompanied by a significant incidence of toxicity (Amrein & Weitzman, 1985) that is often acceptable but sometimes severe, depending on the dose (Merlano et al, 1987) or the specific site (Kies et al, 1987).One of the major objectives of clinical pharmacokinetics is to improve the therapeutic index on an individual patient basis. For a limited population of head and neck carcinoma patients treated by CDDP-5-FU, we previously showed that the digestive tract and/or haematological tolerance was linked to the degree of total body exposure to the drug during the cycle (C xT, area under curve, AUC) (Thyss et al, 1986a).…”
mentioning
confidence: 99%
“…In squamous cell carcinoma of the head and neck very high response rates have been observed when the drug is combined with cisplatin (CDDP) (Thyss et al, 1986b;Amrein & Weitzman, 1985;Kish et al, 1982). This combination protocol is accompanied by a significant incidence of toxicity (Amrein & Weitzman, 1985) that is often acceptable but sometimes severe, depending on the dose (Merlano et al, 1987) or the specific site (Kies et al, 1987).…”
mentioning
confidence: 99%
“…Several kinds of combination therapy have been employedbut the reported objective response rates have been 15% with CDDPand bleomycin (12), 42% CDDPand mitomycin (13), 29% with CDDP, bleomycin and vindesine (14), and 35 to 60% with CDDPand 5FU (1,(15)(16)(17)(18), respectively. Cure is not possible and the prognosis for esophageal carcinomapatients remains unsatisfactory.…”
Section: Discussionmentioning
confidence: 99%